The Pork Food Chain as a Route of Transmission of Antimicrobial Resistant Escherichia coli: A Farm-to-Fork Perspective - Martina Rega; Laura Andriani; Antonio Poeta; Silvia Bonardi; Mauro Conter; Cristina Bacci (MDPI AG, 2023)
Antimicrobial resistance (AMR) is a public health risk that needs to be faced from a One Health perspective that includes humans, animals, and environmental health. The food production chain has been identified as a possible route of transmission of AMR bacteria to humans. The most critical phenomenon is related to Critically Important Antimicrobial (CIA) resistance. β-lactams antibiotics (cephalosporin of 3rd, 4th generation, carbapenem, monobactams, and penicillins), quinolones, aminoglycosides, polymyxin, and glycylcyclines were the CIAs chosen in this study. Samples derived from all the stages of the pork food production chain were collected, including pig feces, carcasses, and pork food products (fresh meat, fermented, and seasoned). Escherichia coli were isolated, and AMR and MDR profiles were evaluated. Enterobacterial Repetitive Intragenic Consensus (ERIC-PCR) was used to evaluate phylogenetic similarities. Data showed that 50% of phenotypical AMR observed in the entire pork food chain were related phylogenetically. The contamination of fresh meat, in half of the cases, was not directly related to contamination from feces or carcasses. Despite this, some similarities were found between feces and carcasses. In group analysis, phylogenetic similarities were detected in a 3/36 cluster (8.3%). Nevertheless, further studies are needed to improve consumer risk communication and access to clear and reliable information and health concerns on food labels.